Pengaruh Kebijakan Hutang Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderating - Bakti Nugraha, Alfian; Akhmadi, Akhmadi (GEMA EKONOMI, 2023)
This study aims to examine the effect of debt policy on firm value moderated by dividend policy. As an additional analysis, this research will also examine the role of downstream mining and the COVID-19 pandemic in moderating the effect of debt policy on company value. The approach used in this research is a quantitative approach. The research sample consisted of nine mining companies listed on the IDX for the period 2018 - 2022. The research data is secondary data which is then analyzed using the panel regression analysis technique. The results of this study indicate that debt policy has a negative effect on firm value. The results of this study also indicate that dividend policy can weaken the effect of debt policy on firm value. Further analysis in this study regarding the role of mining downstream and the Covid 19 pandemic in moderating the effect of debt policy on company value shows the result that mining downstream can weaken the decline in company value due to high debt policy, while the Covid 19 pandemic can strengthen the influence of debt policy on company value